1997
DOI: 10.1007/s004240050391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide on force-generating proteins of skeletal muscle

Abstract: Nitric oxide (NO) has recently been identified as a physiologically important intracellular messenger modulating the contractile activity of skeletal muscle [Kobzik L, Reid MB, Bredt DS, Stamler JS (1994) Nature 372: 546-548]. However, the mechanism of action of NO is not yet known. We used skinned (demembranated) muscle fibres to investigate the mechanism of NO function in muscle contraction. Maximally Ca2+-activated single fibres of rat skeletal muscle were exposed to physiologically relevant NO concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
3
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 19 publications
(30 reference statements)
1
47
3
5
Order By: Relevance
“…Nitric oxide (NO) is known to decrease shortening velocities in both vertebrate skeletal and cardiac muscle fibres (Galler et al, 1997;Perkins et al, 1997). Recently, Evangelista et al demonstrated that NO acts directly on skeletal and alpha-cardiac myosin heavy chains by S-nitrosylating cysteine residues in the myosin heavy chain, resulting in slowed actin velocity in an in vitro motility assay and increased myosin force production in a laser trap (Evangelista et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) is known to decrease shortening velocities in both vertebrate skeletal and cardiac muscle fibres (Galler et al, 1997;Perkins et al, 1997). Recently, Evangelista et al demonstrated that NO acts directly on skeletal and alpha-cardiac myosin heavy chains by S-nitrosylating cysteine residues in the myosin heavy chain, resulting in slowed actin velocity in an in vitro motility assay and increased myosin force production in a laser trap (Evangelista et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the decreased ATP turnover occurring after nitrate supplementation might be related to a reduced ATP requirement for actin-myosin cross-bridge cycling and/or calcium handling, given previous reports that NO slows actin-myosin cross-bridge cycling [59,60] and inhibits calcium-ATPase activity [61,62]. Interestingly, a recent murine model investigation reported greater force production, and increased expression of the calcium handling protein calsoquestrin 1 and the dihydropyridine receptor in type II muscle fibres following nitrate supplementation [9].…”
Section: Effect Of Nitrate Supplementation On Cardiorespiratory Variamentioning
confidence: 99%
“…Galler et al (21) showed NO-depressed muscle contrac-tion in regard to both mechanical properties and myofibrillar ATPase activity using the skinned fibers method. Aghdashi et al (22) hypothesized that oxidants and NO interact directly with Ca 2ϩ release channel (ryanodine receptor 1) in the Tsystem.…”
mentioning
confidence: 99%